Soybean nodulation and yield when co-inoculated with Bacillus subtilis and Bradyrhizobium japonicum / bradyrhizobium elkanii - Araújo, Fábio Fernando de; Hungria, Mariangela (Pesquisa Agropecuaria Brasileira, 1999)
Bacillus subtilis can improve rhizobial symbiotic performance by inhibiting plant pathogens or by the exudation of hormones. To verify the viability of co-inoculation of soybean seeds with Bradyrhizobium and Bacillus, three experiments were performed, in the State of Paraná, Brazil, in soils with established population of Bradyrhizobium. The Bradyrhizobium strains SEMIA 5019 and SEMIA 5080, and their natural variant strains tolerant to the metabolites of Bacillus were co-inoculated with two strains of Bacillus (AP-3 and PRBS-1), or their metabolites. In 1993/94, in Londrina, the co-inoculation of Bradyrhizobium with formulated metabolites increased significantly, in relation to non-inoculated control, nodule number (59%, stage V3), nodule occupancy by Bradyrhizobium strains carried on the inoculant (76%, R2) and soybean yield (24%); in Ponta Grossa, these increases were of 60%, 145% and 22%, respectively. Also in Londrina, the co-inoculation of the variant strains with crude metabolites of Bacillus has also increased yield (26%) and total N in grains (17%) and increases were verified by the co-inoculation of the Bradyrhizobium variant strains with Bacillus cells (78%). Consequently, the results have shown the viability of co-inoculating soybean seeds with crude or formulated metabolites, or with cells of Bacillus subtilis, to increase the contribution of the biological nitrogen fixation process.
Keywords: biological control; biological nitrogen fixation; Glycine max; inoculation; inoculant